Abnormal skeletal muscle bioenergetics in familial hypertrophic cardiomyopathy. Issue 2 (August 1997) - Thompson, C. H.; Kemp, G. J.; Taylor, D. J.; Conway, M.; Rajagopalan, B.; O'Donoghue, A.; Styles, P.; McKenna, W. J.; Radda, G. K.
Abstract : OBJECTIVE: To determine the skeletal muscle metabolic manifestations of familial hypertrophic cardiomyopathy. DESIGN: A case-control study. SETTING: 31P magnetic resonance spectroscopy of the calf muscle was performed on volunteers from a centre specialising in familial hypertrophic cardiomyopathy. PATIENTS: Five patients with abnormal beta myosin heavy chain protein in cardiac and skeletal muscle and five patients with a troponin T abnormality in cardiac muscle were compared with healthy controls. RESULTS: High energy phosphate metabolism in vivo was examined in a non-invasive manner. In resting muscle, the beta myosin heavy chain group had a higher ratio of phosphocreatine to ATP concentration (4.51 (SD 0.17)) than either the troponin T group (3.88 (0.42)) or controls (n = 16; 4.04 (0.40)). Exercise duration was reduced compared to controls, and during the fourth minute of exercise phosphocreatine depletion and muscle acidification were greater in both patient groups. After exercise, the recovery of phosphocreatine-an index of oxidative metabolic capacity of the muscle-was slower in the beta myosin heavy chain group (mean half time 0.65 (0.08) minutes) than in the troponin T group (0.60 (0.17) minutes) or controls (0.48 (0.14) minutes). CONCLUSIONS: Exercise metabolism was abnormal in both groups of subjects, and the affected contractile protein determined the metabolic changes in muscle at rest and during recovery. In patients with abnormal beta myosin heavy chain protein, there was a decrease in oxidative capacity consistent with the reduction in mitochondria reported in muscle biopsy studies of similar patients.